PSORI-CM02 Formula Increases CD4+ Foxp3+ Regulatory T Cell Frequency and Ameliorates Imiquimod-Induced Psoriasis in Mice - Chen, Haiming; Liu, Huazhen; Lu, Chuanjian; Wang, Maojie; Li, Xiong; Zhao, Hui; Yan, Yuhong; Yu, Wanling; Han, Ling; Dai, Zhenhua (Frontiers in Immunology, 2018)
Psoriasis is an autoimmune and inflammatory disease, which is estimated to affect two to three percent of the population in the world. PSORI-CM02 is an empirical formula of Chinese medicine optimized from Yin Xie Ling, which is widely used to treat psoriasis in China for decades. However, its anti-psoriatic mechanisms are still not well understood. Here, we explored the therapeutic effects of PSORI-CM02 on psoriasis and its mechanisms of action in imiquimod-induced psoriasis-like mouse models and human HaCaT cells. In experiments in vitro, PSORI-CM02 significantly inhibited HaCaT cell proliferation in dose-dependent and time-dependent manners. Furthermore, it hindered the progression of HaCaT cell cycle and arrested HaCaT cells at G1 phase. On the other hand, our in vivo studies demonstrated that PSORI-CM02 dramatically reduced PASI scores and lesion temperature in imiquimod-induced psoriatic mice. The anti-oxidative activities of GSH, CAT and SOD were increased while oxidative activity of MDA was markedly decreased after treatments with PSORI-CM02. PSORI-CM02 also suppressed the mRNA expression of proinflammatory cytokines, including TNF-α, IL-6 and IL-17, and lowered their protein levels in the serum as well. In addition, PSORI-CM02 could reduce the expression of IKKα and NF-κB in psoriatic skin tissue. It also upregulated the proportion of CD4+Foxp3+ Tregs in both lymph nodes and spleens and promoted CD3+CD25+ Treg proliferation in vitro. Taken together, our research demonstrated that PSORI-CM02 inhibited HaCaT cell proliferation by arresting them at G1 phase and alleviated systemic inflammation and psoriasis in mice via altering the oxidative/anti-oxidative status, tipping the balance between Th17 responsiveness and CD4+Foxp3+ Treg generation, and suppressing the expression of proinflammatory cytokines as well as NF-κB signaling.